Assemblage (JSTOR)
Assemblage is an advanced journal of architectural theory and criticism brought to bear on contemporary practice. Provocative, polemical, and exploratory, Assemblage examines the interrelationships between culture and design, and theory and material reality. Each extensively illustrated issue presents essays, projects, and debates by leading and emerging scholars, theorists, and practitioners. Work is drawn from a wide range of fields: architectural and art history and theory, cultural criticism, literary theory, philosophy, and politics.
Keywords: Architecture & Architectural History